Lahar inundated, modified, and preserved 1.88 Ma early hominin (OH24 and OH56) Olduvai DK site. Issue 116 (March 2018) - Stanistreet, I.G.; Stollhofen, H.; Njau, J.K.; Farrugia, P.; Pante, M.C.; Masao, F.T.; Albert, R.M.; Bamford, M.K.
Abstract: Archaeological excavations at the DK site in the eastern Olduvai Basin, Tanzania, age-bracketed between ∼1.88 Ma (Bed I Basalt) and ∼1.85 Ma (Tuff IB), record the oldest lahar inundation, modification, and preservation of a hominin "occupation" site yet identified. Our landscape approach reconstructs environments and processes at high resolution to explain the distribution and final preservation of archaeological materials at the DK site, where an early hominin (likely Homo habilis ) assemblage of stone tools and bones, found close to hominin specimens OH24 and OH56, developed on an uneven heterogeneous surface that was rapidly inundated by a lahar and buried to a depth of 0.4–1.2 m (originally ∼1.0–2.4 m pre-compaction). The incoming intermediate to high viscosity mudflow selectively modified the original accumulation of "occupation debris, " so that it is no longer confined to the original surface. A dispersive debris "halo" was identified within the lahar deposit: debris is densest immediately above the site, but tails off until not present >150 m laterally. Voorhies indices and metrics derived from limb bones are used to define this dispersive halo spatially and might indicate a possible second assemblage to the east that is now eroded away. Based upon our new data and prior descriptions, two possibilities for the OH24 skull are suggested: it was either entrained by the mudflow from the DK surface and floated due to lower density toward its top, or it was deposited upon the solid top surface after its consolidation. Matrix adhering to material found in association with the parietals indicates that OH56 at least was relocated by the mudflow.